PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK SEMONGKAT - Roos Nana Sucihati; Dedi Susanto; Rizki Nandasari (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
This study aims to examine the effect of product quality, price and promotion on the purchasing decisions of Semoangkat brand bottled water among consumers in Brang Biji Village, Sumbawa Regency. This type of research is associative which aims to determine the relationship between variables product quality, price and promotion on the purchase decision. The type of data used in this study is quantitative data obtained from primary sources, namely consumers of bottled water with the semoangkat brand in Brang Biji Village, Sumbawa Regency. the sample in this study amounted to 71 people. Researchers use a questionnaire or questionnaire to collect data. The results of data collection will be processed using the SPSS program and studied using techniques that include simple linear regression analysis, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that product quality, price and promotion have a positive and significant effect on the purchasing decision of Semongkat brand bottled water for consumers in Brang Biji Village, Sumbawa Regency, both partially and simultaneously. The degree of influence of product quality, price and promotion simultaneously has a significant effect on the decision to purchase packaged drinking water with the Semongkat brand for consumers in Brang Biji Village, Sumbawa Regency, which is 83.8%, while the remaining 16.2% is influenced by other variables outside the research model. such as service, brand image and others.